Influence of low-temperature annealing on mechanical properties and grain-subgrain structure of submicrocrystalline nickel samples; Modern technique and technologies MTT' 2012 - Sanarova O. G. (Section XII: Nanomaterials, Nanotechnologies and New Energetics, 2012)
Заглавие с титульного листа